2008
DOI: 10.3354/ame01162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the polychaetes Arenicola marina and Nereis diversicolor on microbial pyrene mineralization

Abstract: The effects of 2 polychaetes, Nereis diversicolor and Arenicola marina, on the microbial mineralization of the organic contaminant pyrene, a polycyclic aromatic hydrocarbon (PAH), were followed over 44 d. We also examined whether the effect of the polychaetes was caused by enhanced oxygen supply, altered pyrene bioavailability and/or a changed abundance or activity of pyrenedegrading bacteria. The presence of polychaetes enhanced microbial pyrene mineralization by 180 to 200% compared with defaunated sediment.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2010
2010
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 34 publications
0
5
0
2
Order By: Relevance
“…An increase of nematode abundance resulted in higher organic matter mineralization (Nascimento et al 2012). It has been reported that the presence of polychaetes enhanced microbial pyrene mineralization, probably by increasing oxygen supply due to burrow ventilation (Timmermann et al 2008). In contrast, it was found that the increase of nematode abundance resulted in an increase of hydrocarbonoclastic bacteria grazing and therefore a decrease of PAH degradation efficiency (Naslund et al 2010).…”
Section: Discussionmentioning
confidence: 95%
“…An increase of nematode abundance resulted in higher organic matter mineralization (Nascimento et al 2012). It has been reported that the presence of polychaetes enhanced microbial pyrene mineralization, probably by increasing oxygen supply due to burrow ventilation (Timmermann et al 2008). In contrast, it was found that the increase of nematode abundance resulted in an increase of hydrocarbonoclastic bacteria grazing and therefore a decrease of PAH degradation efficiency (Naslund et al 2010).…”
Section: Discussionmentioning
confidence: 95%
“…It has been demonstrated that oxygen concentrations have a predominant role on the fate of PAHs since the degradation of PAH by microorganisms is much more efficient under aerobic conditions than under anaerobiosis (Boyd et al, 2005;Quantin et al, 2005;Haritash and Kaushik, 2009). Therefore, bioirrigation of sediments by benthic fauna can stimulate PAH degradation through continuous or periodical increase of oxygen availability in anaerobic sediments (Granberg et al, 2005;Timmermann et al, 2008;Montgomery et al, 2008;Cuny et al, 2011). In the present study, we did not detect a stimulation of benzo(a)pyrene loss due to the bioirrigation activity of T. tubifex.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, bioturbation processes such as burrow construction and ventilation carried out mainly by macrofauna are key process to stimulate the availability of oxygen in superficial sediments (Timmermann et al 2008). In addition, some macrobenthic organisms can affect positively the biodegradation of hydrocarbons through the production of digestive compounds acting like surfactants that modify their dispersion state and improve their bioavailability (Penry and Weston 1998;Weston and Mayer 1998;Gilbert et al 2001) for hydrocarbon-degrading bacteria (Bertrand et al 1993;Bonin and Bertrand 1999;Cuny et al 2007;Cuny et al 2011).…”
Section: Resistance Of Macrobenthic Community To Oil Contaminationmentioning
confidence: 99%